The Effect of Travel Vlogs as Electronic Word of Mouth and Destination Image on the Satisfaction and Loyalty of Millennial Tourists Visiting Nusa Penida Island - Andari, Clara Lintang Sistiyo; Wiranatha, Agung Suryawan; Suryawardani, I Gusti Ayu Oka (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 2, Agustus 2023 (pp.187-360)DO - 10.24843/JEKT.2023.v16.i02.p11, 2023)
Satisfaction and loyalty become a measure of the success of a tourist destination. Electronic word of mouth and destination image are two factors that can affect the satisfaction and loyalty of millennial tourists who visit a tourist destination. The purposes of this study were 1) To analyze the effect of travel vlogs as electronic word of mouth on satisfaction and loyalty of millennial tourists visiting Nusa Penida Island, 2) To analyze the effect of destination image on satisfaction and loyalty of millennial tourists visiting Nusa Penida Island, 3) to analyze the effect of satisfaction on the loyalty of millennial tourists who visit Nusa Penida Island. This research was used quantitative method involving 100 respondents who are millennial tourists visiting Nusa Penida Island. Sampling was done by purposive sampling method and analysis using Structural Equation Model (SEM) with SmartPLS 3.0 software. The results showed that 1) travel vlog as electronic word of mouth had significant effect on satisfaction and destination image had significant effect on satisfaction 2) travel vlog as an electronic word of mouth had significant effect on loyalty and destination image had not significant effect on loyalty, 3) Satisfaction had significant effect on loyalty. Other results showed that 81% of millennial tourists use social media as a source of information about Nusa Penida Island.